2015
DOI: 10.4103/0972-124x.157879
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of nicotine and metabolites on the periodontal status and the mRNA expression of interleukin-1β in smokers with chronic periodontitis

Abstract: Background and Objective:Smoking is an important environmental risk factor involved in the causation and progression of periodontal disease. Smoking can impair various components of the host immune response and immune system. The virulence factors of periodontal pathogens stimulate inflammatory cytokine expression by mononuclear cells. IL-1β is the key mediator involved in the pathogenesis and disease progression. Therefore, whole gingival biopsy samples are assessed for this increased expression of IL-1.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…A total of 2,763 studies were identified from Medline and Scopus, and 1,934 studies remained after removing duplicates. Of these, 1,878 studies were ineligible for reasons described in Figure , leaving 56 that were eligible for review. Six studies were excluded because of insufficient data after contacting the authors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 2,763 studies were identified from Medline and Scopus, and 1,934 studies remained after removing duplicates. Of these, 1,878 studies were ineligible for reasons described in Figure , leaving 56 that were eligible for review. Six studies were excluded because of insufficient data after contacting the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 50 studies, 45 objectively assessed OH using an oral examination. Of these 45 studies, 15 analysed OH as categorical data, 31 as continuous data and one as both. Eleven studies provided the association between periodontitis and oral care habits measured according to the frequency of brushing, interdental cleaning and dental visits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The host inflammatory response to smoking and periodontopathogens is considered a major causative factor in the local tissue destruction observed in periodontitis [12,13]. The association of smoking status with periodontal destruction can thus be correlated with the increased mRNA expression of IL-1β [14]. Nicotine induces the production of IL-1β and IL-8 via the α7 nAChR/NF-κB pathway in human periodontal ligament cells [15], and through this pathway, it induces osteoclastogenesis and osteoclast activation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking was associated with the mRNA expression of IL-1 β using real-time PCR in chronic periodontitis patients. [ 75 ] The expression of specific micro RNA species in periodontitis targeting and modulating cytokine mRNA using quantitative micro RNA PCR assay which provides insights to modify periodontal inflammation. [ 76 ] Quantitative mRNA expression of various growth factors; receptors toll-like receptors (TLRs), NOD2 and NALP3; signaling mediators CD14, MYD88, and TIR-domain-containing adapter-inducing interferon-beta were also determined by RT-PCR.…”
Section: Applications In Periodontologymentioning
confidence: 99%